The moderating effect of religiosity on ethical behavioural intentions: An application of the extended theory of planned behaviour to Pakistani bank employees - Kashif, Muhammad; Zarkada, Anna K.; Thurasamy, Ramayah (My University, 2017)
Purpose: The purpose of this paper is to investigate Pakistani bank front-line employees’ intentions to behave ethically by using the extended theory of planned behaviour (ETPB) into which religiosity (i.e. religious activity, devotion to rituals and belief in doctrine) is integrated as a moderating variable. Design/methodology/approach: The authors collected 234 self-administered questionnaires and analysed them using SmartPLS 2.0, a second generation structural equation modelling technique. Findings: This paper demonstrates that the ETPB can explain intentions to behave ethically. Moral norms (i.e. the rules of morality that people believe they ought to follow) and perceived behavioural control (i.e. people’s perceptions of their ability to perform a given behaviour) are the best predictors of ethical behavioural intentions. The effects of injunctive norms (i.e. perceptions of which behaviours are typically approved or disapproved in an organisation) and of perceived behavioural control on behavioural intent are moderated by religiosity. Practical implications: Leading by example, providing ethics training, empowering employees and encouraging the expression of religiosity are proposed as ways to foster an ethical culture in the workplace. Originality/value: Even though numerous empirical studies have utilised variants of the theory of planned behaviour to explain consumer behaviour, its applicability to ethical behaviour in the workplace has scarcely been explored. Moreover, its tests in non-western contexts are scant. This study demonstrates the applicability of the ETPB in a broader circumstantial and cultural context and enriches it with religiosity, a pertinent characteristic of billions of people around the world. Finally, this is one of the very few ethics studies focusing on banking, an industry fraught with allegations of moral breaches.
Keywords: Pakistan; Ethics; Banking; Quantitative; Religiosity; ETPB; Front-liners